Structural and Geochemical Interactions Between Magma and Sedimentary Host Rock: The Hovedøya Case, Oslo Rift, Norway. (16th March 2020) - Poppe, S.; Galland, O.; de Winter, N. J.; Goderis, S.; Claeys, P.; Debaille, V.; Boulvais, P.; Kervyn, M.
Abstract: Two end‐member conceptual models are used to describe deformation of the Earth's crust induced by magma intrusion. "Mode I" fracturing assumes tensile or opening‐mode, elastic deformation, while "Mode II" fracturing assumes plastic shear‐mode deformation around a viscous indenter. Field observations of both mechanisms exist, but it remains unclear which mechanism dominates in which conditions. We describe intrusion geometries, host rock deformation, and geochemical magma‐host rock interactions around 53 exceptionally preserved, tephrite‐basanite Permian dike segments of 0.5‐ to 30‐cm thickness. These thin dikes, that is, "dikelets, " intruded Late‐Ordovician carbonate‐rich sedimentary rocks on Hovedøya island, Oslo Rift, Norway. Dikelets emplaced in preexisting fractures dominantly created cavities ahead of their narrow, tapering tips and are associated with bent host rock, broken bridges, and stepped segmented geometries. Other tips are blunt with dense brittle fracturing around them. Also, cross‐sectional intrusion segment opening profiles deviate from parabola‐shaped profiles typical for elastic media. The observations demonstrate that dominant opening‐mode host rock deformation can coexist with shear‐mode deformation locally. Alignment of most dikelet segments along the dominant host rock fracture directions highlights the control of local structural orientations on magma emplacement. Analysis of bulk major and trace element compositions, in situ micro‐XRF sample analysis and carbon and oxygen stable isotope compositions, suggests that thermochemical interactions between magma and the carbonate‐rich host rock produced a low‐viscosity mixture of magma, pore water, and gas. We propose that such low‐viscosity hybrid fluid may assist in the intrusion of magma in sedimentary rocks by filling the cavity ahead of propagating sheet intrusion tips. Plain Language Summary: When molten rock, or magma, ascends through the Earth's crust, it creates space for itself by deforming the host rock around it. With elastic deformation, rock bends but returns to the initial state after the deformation source is removed. With plastic deformation, the rock breaks and is thus structurally altered. We studied the deformation caused by numerous 0.5‐ to 30‐cm thick magma intrusions in a rock sequence exposed on Hovedøya island, Norway. The observed geometries of the majority of the intrusion tips and the deformation structures around them suggest dominant elastic deformation of the host rock. Intrusion thickness profiles and the blunt geometry of a minority of tips suggest that plastic deformation occurred as well. Fractures that were present in the host rock before magma was emplaced controlled the orientation of the magma emplacement. Finally, geochemical analysis suggests that thermal and chemical interaction between the hot magma and the cold host rock produced a mixture of fluid and gas during or shortly after magma intrusion. Our observations suggest that elastic and plastic deformation of a sedimentary host rock by magma can coexist and is affected by structural weaknesses in the host rock and thermochemical processes. Key Points: Dikelets intruded calcareous sedimentary rock at Hovedøya dominantly by opening‐mode fracturing but additional shear‐mode fracturing Preexisting fractures controlled the magma propagation orientation Thermochemical magma‐host rock interaction produced a low‐viscosity magma‐water mixture and gas that propagated ahead of the magma